Nyinglar Sasalad Ceremony as a Local Wisdom of Cireundeu Indigenous Group in Dealing with Covid-19 - Sofiana, Neng Eri; Sunni, Muhammad Ismail; Wijaya, Angga Kusuma (Center for Research and Development of Religious Literature and Heritage, 2022)
Cireundeu village, a traditional village in South Cimahi West Java Indonesia has its own unique way of coping with Covid-19 pandemic. Despite being a traditional village, the residents of Cirendeu are in high mobility as workers in the nearby city, hence the exposure to Covid-19 was quite present. This article explores how the Cireundeu indigenous group dealt with the Covid-19 pandemic. This study employed a qualitative approach, particularly descriptive method. The data was conducted mainly by interviews with community figures. ”˜Governing the common’ by Ostrom (2000) was used as a theoretical lens in analysing the data. This study found that the traditional group in Cireundeu were able to manage their local resources (from the nearby forests) for the benefit of their community members. They performed Nyinglar Sasalad ceremony as a symbol of communal attitude towards the plague, complemented with herb and Rasi (cassava-made rice) consumption to strengthen the immune defence. This study is expected to be a reference for a mitigative action in dealing with pandemic through the use of local tradition and ways of living.